Simultaneous determination of PT, PD, RH and IR traces in environmental samples by flow injection solid phase extraction coupled with online inductively coupled plasma atomic emission spectroscopy (ICP-AES) - Calvo-Fornieles, Ana; García-de-Torres, Amparo; Vereda-Alonso, Elisa Isabel; Cano-Pavón, José Manuel (My University, 2014)
An increased worldwide usage of platinum group elements (PGEs) has been observed during the last twenty years due to their applications in areas such as chemical industry, metallurgy, jewelry production, dental devices, anti-cancer drug and automobile catalytic converter systems. These applications were found to be anthropogenic sources of pollution of these elements nowadays. The presence of PGEs in different environmental and biological materials is a risk to ecological and human health because may be easily mobilized and solubilized in several matrices. The determination of Pt, Pd, Rh and Ir presents difficulties because of the low concentrations of these metals in environmental samples and the numerous interactions between the analytes and the matrix constituents, which can significantly influence both the limit of detection and the accuracy of determination in complex samples. Initial sample pretreatment such as pre-concentration of these elements and matrix separation are often necessary. Numerous reviews devoted to PGEs determination have been published; however, they deal mainly with techniques used for analytical signal formation and less with pre-concentration and separation procedures which usually precede the quantification of the analyte by spectrometric techniques [1]. In this work, Pt, Pd, Rh and Ir have been simultaneously determined by flow injection solid phase extraction coupled online with ICP-AES. The system is based on the retention of the analytes onto a minicolumn filled with a chelating exchange resin placed in the injection valve of a simple flow manifold. This configuration offers several advantages, including (a) elimination of the matrix effect, (b) increase the sensitivity by the preconcentration and, (c) automatization of the different steps. The effects of chemicals and flow variables were investigated. The optimized operating conditions selected were: sample pH 7.5, sample flow rate 2.2 mL min-1, eluent flow rate 0.9 mL min-1, eluent 0.07% thiourea in 2M HCl. With these conditions, the enrichment factors obtained were 6.3, 6.7, 3.7 and 6.3 for Pt, Pd, Rh and Ir respectively. Detection limits (3 min sample loading time) were 1.4 µg L-1 for Pt, 0.5 µg L-1 for Pd, 256 µg L-1 for Rh and 0.6 µg L-1 for Ir. The accuracy of the proposed method was checked with the certified reference material NIST-2557 autocatalyst. The results obtained using this method were in good agreement with the certified values of the standard reference material. The method was applied to the determination of Pt, Pd, Rh and Ir in different sea-water samples collected in Málaga, Spain. [1] B. Godlewska-Zylkiewicz, Microchim. Acta 147 (2004) 189.
Keywords: Grupo del platino; Platinum Group Elements; ICP-AES; Solid phase extraction; Environmental samples